Penentuan Perlakuan Terhadap Kawasan Perguruan Tinggi Jatinangor Menurut Persepsi Mahasiswa: Suatu Pendekatan Konsep Pemasaran - Ratih Wulandari; Ridwan Sutriadi (The Institute for Research and Community Services, Institut Teknologi Bandung, 2004)
Infrastructure, unemployment, and other social issues in Jatinangor may potentialy reduced the image of Jatinangor as a university town and implied the decline of the land value. Many concepts have been tried to solve the problems declining image Jatinangor. One of the concept that can be applied on Jatinangor is city marketing, a concept introduced by Philip Kotler and also Ashworth and Boogd. City marketing is a private sector's concept which is adapted to public sector. This paper proposes a city marketing's approach to solve the problem of Jatinangor by exploring the perception of university's student in Jatinangor based on two criteria: performance and importance.